Personal time management - Haynes, Marion E. (Crisp Pub. Menlo ParkUS, 1994)
Proposes three main time management techniques namely: establishing priorities; eliminating unnecessary tasks; and making daily and weekly time plans. Suggests sub-tasks including delegating, and reducing distractions. Devotes one chapter each to time saving electronics, and time saving tips for travellers. Provides an action plan for applying theory to daily practice.